The Dynamics of Ethical Leadership Enhance Customer Orientation in a Competitive Marketplace - Nick, Sehrish; Larry, Cristina; Costa, Eliana (Journal Economic Business Innovation, 2025)
Purpose: This study explores ethical leadership dynamics (humane, justice, and moderation leadership) that strengthen customer orientation (CO) under competition environments within Australia. This study seeks to deepen the understanding of how leadership behaviors affect CO at different stages of competitive intensity.Methods: A quantitative approach using survey data collected from 700 managers in a variety of industries in Australia. To test the hypotheses, structural equation modeling (SEM) was employed, as well as interaction analysis to assess competitive intensity as a moderator.Results: All three ethical leadership styles significantly promote CO, and moderation leadership is more significantly and positively related to CO than the other two leadership styles. The competitive intensity adds an extra layer to these effects, highlighting that competitive and dynamic contexts make leadership behaviors vital. Synergistic relationships among leadership styles, CO, and competitive intensity are illustrated in interaction plots.Novelty: Previous research examined mostly not all ethical leadership in isolation and this study integrates several ethical leadership styles to understand their collective and individual effects on CO. Moreover, this study expands understanding regarding the dynamics of leadership in the context of real-world competition by introducing competitive intensity as a contextual moderator.Implications: The study provides actionable insights for organizations seeking to develop customer-centric organizations. Leadership training programs should focus on ethical leadership behaviors, especially in highly competitive industries. On an academic front, this research fills the void in literature by showing the metanarrative of the role between ethical leadership styles and environmental aspects.